PENGARUH TINGKAT KONSUMSI ENERGI, PROTEIN, LEMAK, DAN STATUS KECACINGAN TERHADAP STATUS GIZI PADA SISWA SEKOLAH DASAR NEGERI 01 LIMPAKUWUS - Manuhutu, Rendy; Purnamasari, Dyah Umiyarni; Dardjito, Endo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
School age is the important period of human life and the quality have to be prepared well. The school age children is susceptible to malnutrition. Malnutrition among school age children will implicatethe children?s development and further potential development in that age. Food consumption levels and worm infection status are the two most affected factors to nutritional status of children school. The purpose of this research is to know the effect of energy, protein, fat and worm inflectional status to the nutritional status of SDN 01 Limpakuwus?s student in Sumbang, Banyumas. This research was cross sectional study approach,used purposive sampling with inclusion and exclusion criteria in 44 respondents. Analysis conducted by univariate, bivariate (Spearman rank) and multivariate (multiple logistic regression).Multivariate analysis showed the variables that influenced nutritional status is the level of fat consumption (p=0.022), and the variable did not affect the nutritional status are the level of energy consumption (p=0.999), protein consumption level (p=0.580), and worm infection status (p = 0.661). The suggestion is to get more food that can fulfil the energy, protein, fat needs and make the canteen in the school becomes a healthy canteen that serves healthy and nutritious meal.